2019
DOI: 10.1210/js.2019-00263
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Management of Acute Addison Disease: Audit of Patients Attending a Referral Hospital in a Regional Area

Abstract: Context Adrenal crisis (AC) causes morbidity and mortality in patients with Addison disease [primary adrenal insufficiency (PAI)]. Patient-initiated stress dosing (oral or parenteral hydrocortisone) is recommended to avert ACs. Although these should be effective, the continued incidence of ACs remains largely unexplained. Methods Audit of all attendances between 2000 and 2017 of adult patients with treated PAI to one large re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
1
13
0
1
Order By: Relevance
“…Unlike stress dose use in CAH patients drawn from the same general population, there was no relationship with patient age and use of dose escalation strategies 12 . Previous attendance for an acute illness was found to be positively associated with the use of dose escalation prior to hospital in these patients, which is consistent with the evidence from other studies and suggests that lived experience of an acute illness episode is an important element in the development of competency in self‐management in AI patients 12,25,26 …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Unlike stress dose use in CAH patients drawn from the same general population, there was no relationship with patient age and use of dose escalation strategies 12 . Previous attendance for an acute illness was found to be positively associated with the use of dose escalation prior to hospital in these patients, which is consistent with the evidence from other studies and suggests that lived experience of an acute illness episode is an important element in the development of competency in self‐management in AI patients 12,25,26 …”
Section: Discussionsupporting
confidence: 80%
“…12 Previous attendance for an acute illness was found to be positively associated with the use of dose escalation prior to hospital in these patients, which is consistent with the evidence from other studies and suggests that lived experience of an acute illness episode is an important element in the development of competency in self-management in AI patients. 12,25,26 Children with comorbid DI were found to have more attendances with electrolyte derangements including hypernatremia and hyponatraemia. They also were found to have a higher number of episodes with blood glucose levels lower than 3.5 mmol/L, a phenomenon that may be related to lower levels of circulating cortisol in the context of a lower frequency of stress dose use in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Hyponatraemia (serum sodium less than 135 mmol/L) was found in 48.7% (n = 74) and hyperkalaemia (serum potassium greater than 5.0 mmol/L) in 21.1% (n = 32). The distribution of other relevant clinical details for these patients was reported previously 10 …”
Section: Resultsmentioning
confidence: 85%
“…The design of the study and the description of the PAI patient population have been reported previously 10 . Briefly, the study comprised a retrospective audit of the medical records of patients with at least one admission to a large regional hospital in which there was a principal or comorbid diagnosis of PAI 10 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation